Epilepsy and proxy‐reported health‐related quality of life in children and young people with non‐ambulatory cerebral palsy. (12th July 2022) - Ostendorf, Adam P.; Axeen, Erika T.; Eschbach, Krista; Fedak Romanowski, Erin; Morgan, Lindsey A.; Gross, Paul; Narayanan, Unni G.; Glader, Laurie; Noritz, Garey; ,
Abstract: Aim: To assess the association between epilepsy characteristics and proxy‐reported health‐related quality of life (HRQoL) in children and young people with non‐ambulatory cerebral palsy (CP) and seizures. Method: This was a cross‐sectional study of 164 children and young people (74 females, 90 males; mean age 10 years 6 months, range 2–21 years, SD 5 years 5 months). Caregivers completed the Child Health Index of Life with Disabilities (CPCHILD) in an outpatient setting. We utilized univariable linear regression and multivariable modeling to study relationships between variables and CPCHILD scores. Results: Gross Motor Function Classification System levels were 37% IV and 63% V. Sociodemographic factors included the Child Opportunity Index (median 51, interquartile range [IQR] 25–80). A median of 2 (IQR 1–3) antiseizure medications (ASMs) were used, and days with seizures ranged from 0 (30%) to 28 (20%) days in the previous 4 weeks. Total CPCHILD scores decreased 2.3 points for each ASM (95% confidence interval [CI] –4.1 to −0.42). Compared to persons with focal epilepsy, those with generalized epilepsy had lower total CPCHILD scores (−5.7; 95% CI –11 to −0.55). Number of days with seizures was not associated with total CPCHILD scores. Interpretation: Proxy‐reported HRQoL was affected by epilepsy‐specific features in children and young people with severe CP. What this paper adds: Health‐related quality of life (HRQoL) was lower with increasing numbers of antiseizure medications. Overall quality of life (QoL) scores were lower by a similar amount, independent of seizure frequency. HRQoL was lower in persons with recent hospital admissions for epilepsy. What this paper adds: Health‐related quality of life (HRQoL) was lower with increasing numbers of antiseizure medications. Overall quality of life (QoL) scores were lower by a similar amount, independent of seizure frequency. HRQoL was lower in persons with recent hospital admissions for epilepsy. The association between epilepsy characteristics and health‐related quality of life was assessed in 164 children and young people with non‐ambulatory cerebral palsy and epilepsy utilizing the Child Health Index of Life with Disabilities (CPCHILD). Total CPCHILD scores decreased across all degrees of seizure burden by a similar amount. Independently, total CPCHILD scores were lower in those taking more antiseizure medications.